PERSEPSI MASYARAKAT TERHADAP APLIKASI TIKTOK SEBAGAI MEDIA MENURUNKAN TINGKAT STRES DI ERA PANDEMI COVID-19 - Utama Putra, Kadek Ari Setia; Permana, Gede Wisnu; Sephiani, Putu Yuna; Sutriyanti, Ni Komang (Institut Hindu Dharma Denpasar, 2021)
Social media is a medium for socializing and communicating with each other and is done online which is not regulated by space and time. Social media can be used as a medium to communicate privately and even in groups, share files, videos, music, and so on. Social media which is busy being used to reduce stress in the current pandemic era, one of which is the TikTok application. TikTok is a social media and music video platform from China. This application was first released in September 2016. The purpose of this research is to see the perception of the TikTok application as a medium to reduce stress levels in the Covid-19 pandemic era. Method of collecting data used included interviews, questionnaire questionnaires, documentation, and observation. The data obtained were analyzed using a qualitative descriptive method. The research results are as follows 64% of people say TikTok is a medium for reducing stress. The public accepts and rejects TikTok as the right medium to reduce stress in the Covid-19 pandemic era for various reasons given. From these results it can be ignored that the TikTok application influences TikTok users, both positive and negative. This has led to various responses from the public regarding the TikTok application.